Contribution of the Basilicata region to decarbonisation of the energy system: results of a scenario analysis. (March 2021) - Di Leo, Senatro; Pietrapertosa, Filomena; Salvia, Monica; Cosmi, Carmelina
Abstract: This paper investigates the energy system of the Basilicata region (southern Italy) to highlight, through a scenario analysis, its possible future development in compliance with the European Commission's long-term vision. The IEA-ETSAP methodology was utilized to model and analyse the Basilicata energy system in a business- as -usual scenario, based on the assumptions of the 2010 Regional Energy and Environmental Policy Plan, and in two low-carbon scenarios, decarbonisation and high energy efficiency, which, in line with the long-term European strategy, foresee an 85% carbon dioxide emission reduction and a 20% energy efficiency increase in 2050. The results highlight that electricity production from renewable energy sources (in particular wind energy), strongly supported by the regional policy, goes beyond the Basilicata Regional Energy-Environmental Plan forecast, with a further increase in the decarbonisation scenarios. In addition, solar thermal and highly efficient technologies are adopted in commercial and residential end-use sectors. An additional 9% reduction in energy consumption is achieved in the high energy efficiency scenario by passive houses. The proposed approach shows the usefulness of a modelling framework typically used for national and supranational analyses to support regional authorities in their decision-making process to obtain results in line with the European and national strategies. Application to the Basilicata region shows the usefulness of a consolidated framework for policy assessment at a local scale to assess regional contribution to the achievement of national climate mitigation targets that tend towards climate neutrality. Highlights: The role of regional authorities is essential to reach national decarbonisation goals. TIMES can be advantageously used for regional energy system modelling and analysis. Scenario analysis can be a powerful tool for policy evaluation. A cap on carbon dioxide emissions leads to a 28% increase of electricity production. Passive houses in Residential allow a further 5% reduction of energy consumption.